Differential transcription of ribosomal cistrons denoting nucleolar dominance in hybrids of Drosophila mulleri and Drosophila navojoa (mulleri complex, Repleta group) - Commar, Leliane Silva [UNESP]; Bicudo, Hermione Elly Melara de Campos [UNESP]; Rahal, Paula [UNESP]; Ceron, Carlos Roberto [UNESP] (Sociedade Brasileira de Genética, 2007)
The fruit flies Drosophila mulleri and Drosophila navojoa are included in the mulleri complex of the mulleri subgroup and Repleta group. Although there is no demonstration that interspecific crosses between them occur in nature, they intercross in the laboratory in both cross directions. Previous data have shown the occurrence of nucleolar dominance in interspecific hybrids of some species in the mulleri complex. We investigated nucleolar dominance in D. mulleri/D. navojoa hybrids using the transcription profiles of the rDNA internal transcribed spacer (ITS-1) region. The results showed that the ribosomal cistrons present in the X chromosome and in the microchromosome of D. navojoa are exclusively or preferentially transcribed in these hybrids depending on the cross direction, denoting the complete or partial nucleolar dominance of this species over D. mulleri.
Keywords: Drosophila mulleri; D. navojoa; interspecific hybrids; nucleolar dominance; rDNA